(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The recent demonetisation had very badly affected the construction industry where, almost, all the projects big and small, came to a standstill. The Industry is now fully poised with a renewed vigour for growth. The RERA is imposing stringent regulations on the Builders and any violation is being sternly dealt with. The Buyers are in an advantageous position with more transparency from the builders and also in their fully complying with the prescription of building practice. The small builders who construct up to two floors pay scant attention in adhering to RERA regulations.